Precipitation evolution of Central Asia during the last 5000 years. (January 2017) - Wolff, Christian; Plessen, Birgit; Dudashvilli, Alexey S; Breitenbach, Sebastian FM; Cheng, Hai; Edwards, Lawrence R; Strecker, Manfred R
Central Asia is located at the confluence of large-scale atmospheric circulation systems. However, the number of Holocene climate records is still low in most parts of this region and insufficient to allow detailed discussion and comparisons to disentangle the complex climate history and interplays between the different climatic systems. Here, we present the first stalagmite record from arid Central Asia (south-western Kyrgyzstan) by using δ 18 O, δ 13 C, and micro x-ray fluorescence (µXRF)-sulfur data spanning the last 5000 years. The cave hosting stalagmite Uluu-2 is ideally suited to identify past shifts in seasonal variations in precipitation in this part of the world. Comparison of instrumental and paleo-isotopic studies demonstrates that the Uluu-2 speleothem isotope composition faithfully records climate changes and responds to shifts in the proportion of moisture derived from mid-latitude Westerlies during the winter/spring season. The reconstructions suggest that the area was characterized by a dry climate from 4700 to 3900 yr BP, interrupted by a wet episode around 4200 yr BP. Further drier conditions also occurred between 4000 and 3500 yr BP. Wetter conditions were re-established at ca. 2500 yr BP, after another dry episode between 3000 and 2500 yr BP. With the exception of two short dry events (1150 and 1300 yr BP), the period after 1700 yr BP shows moderate to wet conditions. Regional comparisons suggest that the strength and position of the Westerly winds control climatic shifts in arid Central Asia, leading to complex local responses.